BedKnobs and Broomsticks - Norton, Mary (Jm Dent and Sons Ltd, 1993)
When Miss Price falls off her broomstick it's the start of an amazing adventure for carey, Charles and Paul. Their summer holiday suddenly takes on a new turn when miss price, who is learning to be a witch, cast a spell on their brass bedknob so that its magic can whisk them off anywhere they want.
Keywords: Juvenile literature-Fiction